PEMBENTUKAN KARAKTER TOLERAN ANTAR UMAT BERAGAMA SISWA-SISWI SD NEGERI 3 BANYU BIRU-NEGARA-JEMBRANA-BALI - Dhani Aulia Rohman; Moch Bachrurrosyady Amrulloh (Journal Multicultural of Islamic Education, 2025)
Instilling values ​​of tolerance between religious adherents from an early age is an important strategy in creating a harmonious and inclusive society. This study aims to describe the tolerant character of elementary school students and the process of character formation in the school environment. The approach used is descriptive qualitative, with data collection through observation, interviews, and documentation in several elementary schools with a background of religious diversity. The results of the study show that tolerant character is evident in students' daily behavior, such as attitudes of helping each other, working together, respecting differences, and reminding each other in terms of goodness. The process of forming this attitude is carried out through activities such as interfaith prayer together, providing advice and role models from teachers, and providing freedom for students to practice their respective beliefs. A conducive school environment, the role of teachers as role models, and healthy social interactions are important factors in strengthening attitudes of tolerance between students. These findings emphasize the urgency of character education that integrates diversity values ​​at the elementary school level.